영어 관계사절 습득 과정에서 한국 L2 학습자들의 공백에 대한 민감성 연구 - 조우영; Cho Wooyoung (언어학, 2021)
The purpose of this paper is twofold: (1) to explore the Korean L2 learners' acquisition order of 9 types of English relative clauses, classified by the grammatical role of both the head (nominal that the relative clause modifies) and the gap within the relative clauses; and (2) to examine the correlation between Korean L2 learners' comprehension and the distribution of relative clauses in English textbooks. Eighty Korean middle school students participated in the experiment. The major findings of this experimental study are as follows: First, the order of comprehension is SO> OO > OS > SS, which is not similar to those shown in the previous studies. Second, the embedded depth of subject gaps as well as word order of L1 made Korean L2 learners difficult to comprehend English relative clauses. Third, both the distribution and the frequency of relative clauses in English textbooks seem not to reflect the comprehension pattern of Korean L2 learners properly.